Wellbeing, mastery and work participation: Effects of the Five Ways to Wellbeing course—a randomized controlled trial - Maja Eilertsen; Nikolai O. Czajkowski; Tone K. Omsland; Espen Røysamb; Ragnhild Bang Nes (Scandinavian Journal of Public Health, 2026)
Background: Rising ill health, declining wellbeing, and absenteeism threaten societal sustainability amid an ageing population. Promoting health, wellbeing and work participation is essential. The Five Ways to Wellbeing course is a six-week programme designed to enhance wellbeing through five core activities: connecting, being active, taking notice, learning, and giving. A digital, shorter version has shown effectiveness in the general population, but the physical course has not been evaluated by randomized controlled trial in high-risk groups. Methods: This parallel two-group randomized controlled trial examined the effects of the Five Ways to Wellbeing course versus no course. Adults (⩾18 years old) receiving benefits through the Norwegian Labour and Welfare Administration were randomly assigned to the intervention or control group. The trial was non-blinded; participants were aware of group allocation because blinding was not feasible. Main outcomes were wellbeing, mastery and work participation, measured at baseline, post-intervention and six months. Multilevel analyses compared repeated measures across groups. Results: A total of 171 adults were randomized to the intervention ( n = 87) or the control group ( n = 84). Owing to attrition, data from 71 intervention and 46 control participants were included in the final analyses. No statistically significant differences in wellbeing, mastery or work participation were observed between groups. Conclusions: This underpowered trial found no statistically significant effects, limiting conclusions about the course’s effectiveness. However, it provides insight into the challenges of conducting pragmatic randomized trials within routine welfare services. Trial registration: ClinicalTrials.gov (ref. NCT04668560).